2011
DOI: 10.1590/s1980-65232011000300008
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological evaluation of peracetic acid for disinfection of acrylic resins

Abstract: Purpose: The aim of this study was to assess the efficacy of peracetic acid (PAA) for the disinfection of dental acrylic resins experimentally contaminated with Candida albicans, Escherichia coli, Staphylococcus aureus and Pseudomonas aeruginosa. Methods: Fifteen materials were used for each type of resin (thermosetting, self-curing and microwave-curing). Each material was placed in a test tube containing culture medium with a suspension of each microorganism and then incubated. The materials were rinsed and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 6 publications
1
5
0
2
Order By: Relevance
“…The results of peracetic acid immersion depicted that though the number of colonies were reduced, but complete disinfection was not achieved even after 10 minutes disinfection. The results are supported by the study of Stopiglia et al 21 who concluded in their study that after 5 minutes disinfection with 0.2%, peracetic acid was effective against C. albicans, but was ineffective against E. coli, S. aureus, and P. aeruginosa. 22 Ceretta et al 23 evaluated the effectiveness of peracetic acid in the sterilization of dental equipment and concluded that immersion of the materials in peracetic acid solution at a concentration of 2,500 ppm for 20 minutes promoted complete sterilization.…”
Section: Discussionsupporting
confidence: 64%
“…The results of peracetic acid immersion depicted that though the number of colonies were reduced, but complete disinfection was not achieved even after 10 minutes disinfection. The results are supported by the study of Stopiglia et al 21 who concluded in their study that after 5 minutes disinfection with 0.2%, peracetic acid was effective against C. albicans, but was ineffective against E. coli, S. aureus, and P. aeruginosa. 22 Ceretta et al 23 evaluated the effectiveness of peracetic acid in the sterilization of dental equipment and concluded that immersion of the materials in peracetic acid solution at a concentration of 2,500 ppm for 20 minutes promoted complete sterilization.…”
Section: Discussionsupporting
confidence: 64%
“…Os resultados do ácido peracético, de maneira biocida, são positivos contra Clostridium perfingens e Escherichia coli 25 ; contra Escherichia coli e Salmonella 26 ; contra Staphylococcus aureus meticilina--resistente 27 ; contra colônias de bactérias coletadas em equipos da clínica-escola do Departamento de Odontologia da Universidade Estadual da Paraíba; contra C. albicans 28,29 ; na desinfecção de esgoto sanitário 30 ; contra Candida albicans e Bacillus subtilis 31 ; contra Streptococcus viridans 32 .…”
Section: Discussionunclassified
“…For this methodology, Stopiglia et al was used as reference with adaptations. Eighteen acrylic resin specimens were placed in Sabouraud broth (SB) medium containing 7 × 10 3 CFU/ml of Candida albicans ATCC 10231 and incubated at 37°C for 48 hours.…”
Section: Methodsmentioning
confidence: 99%
“…The analyses were performed before immersion into liquids and in the 4th and/or 12th month. Each week, the specimens were immersed for 30 minutes in the corresponding liquid and then individually washed in an ultrasonic tank for 180 seconds. The liquid used to wash the specimens consisted of 25% detergent and 75% distilled water containing a final volume of 10 mL.…”
Section: Methodsmentioning
confidence: 99%